Estimation of the IL- 33 and TNF-α Levels among Chronic Hepatitis B Virus Patients - Hassoon, Hind Jaber (Iraqi Journal of Science, 2024)
In humans, the hepatitis B virus (HBV) has been demonstrated to be the essential cause of both acute and chronic hepatitis. A variety of cytokines are released as a part of the immune response during HBV infection. The present study aimed to estimate the interleukin-33(IL-33) and tumor necrosis factor-α (TNF-α) in patients with chronic hepatitis B virus (CHBV). This study involved fifty diagnosed CHBV patients (mean age 47.26 ± 14.23) and forty subjects as healthy control (mean age 35.10 ± 9.86). The results revealed by the ELISA method that the serum levels of IL-33and TNF-α were significantly higher (P-value <0.001) in the CHBV patients group (78.12 pg/ml and 15.34 pg/ml respectively) as compared with a healthy control group (20.11pg /ml and 2.91pg/ml respectively). Thus, monitoring these cytokines could be a good strategy that indicates CHBV pathogenesis.